2013
DOI: 10.1038/ajg.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intraductal Papillary Mucinous Neoplasm (IPMN) of the Pancreas: A Multicentre Case–Control Study

Abstract: A previous history of diabetes, especially with insulin use, CP, and family history of PDAC are all relevant risk factors for the development of IPMN. These results suggest an overlap between certain risk factors for PDAC and IPMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 32 publications
3
73
1
2
Order By: Relevance
“…It has been described that previous history of diabetes, especially with insulin dependency, chronic pancreatitis, or a familial history of pancreatic ductal adenocarcinoma (PDAC), may haveahigherriskforIPMN [25]. Also, several studies have noticed that the presence of autoimmune disease in general population is around 5%; however, in patients diagnosed with IPMN, the number rises up to 22%.…”
Section: Risk Factorsmentioning
confidence: 94%
“…It has been described that previous history of diabetes, especially with insulin dependency, chronic pancreatitis, or a familial history of pancreatic ductal adenocarcinoma (PDAC), may haveahigherriskforIPMN [25]. Also, several studies have noticed that the presence of autoimmune disease in general population is around 5%; however, in patients diagnosed with IPMN, the number rises up to 22%.…”
Section: Risk Factorsmentioning
confidence: 94%
“…Capurso et al [10] compared 390 patients with IPMN with 390 matched controls and found that a history of DM, CP, and a family history of pancreatic cancer were all independent risk factors for IPMN. Carr et al [11] examined the association between IPMN malignant progression and smoking in 324 resected IPMNs and found no significant difference in the percentage of invasive IPMNs between smokers and nonsmokers (22 vs. 18%, p = 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the association of environmental, personal, and hereditary risk factors with the occurrence or degree of IPMN [10][11][12][13][14] . Capurso et al [10] compared 390 patients with IPMN with 390 matched controls and found that a history of DM, CP, and a family history of pancreatic cancer were all independent risk factors for IPMN.…”
Section: Discussionmentioning
confidence: 99%
“…Controls were patients seen at the same units' gastrointestinal outpatient clinics during the same time period, for evaluation of different gastrointestinal disorders, with willingness and ability to participate, as previously described [14,25]. We used a frequency matching (oversampling controls with a 4:1 rate) in which every time a case was enrolled and interviewed, the first four eligible controls of the same sex and age (±5 years) were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of smoking was evaluated as pack-years (pack-year = number of packs per day × years of smoking). A cut-off of 20 pack-years was set to define heavy smokers [14,25,26]. …”
Section: Methodsmentioning
confidence: 99%